Industrial Applications of E-Manufacturing - Muhamad, Mohd Razali; Wan Mahmood, Wan Hasrulnizzam (2005)
E-manufacturing is one of the approaches that had been considered important in improving the performance and competitiveness of manufacturing organization. The results of the survey carried out on thirty companies that had received funds for e-manufacturing implementation show that e-manufacturing tools that are more frequently used are the internet and local area network. They are mostly used in product design, demand and inventory management, as well as quality management. The electrical and electronic sector appears to be the bigger user of e-manufacturing in fulfilling the manufacturing strategy criteria.